Pan-African Judgments on the Gulf Investments in Oppressive Governments - Mahmoud, Mahgoub El-Tigani (European Scientific Journal, ESJ, 2017)
The African ancient civilizations played influential roles in global trade and power relations; in recent histories and contemporary times, persistent failures of dependent economies and political leaderships underdeveloped the continent by oppression and manipulative investments. Focusing on the African Charter on Human and Peoples’ Rights, our paper applied a Pan-Africanist framework to assess the impact of Gulf States’ investments on the African setting. The paper stressed the predetermined cycle of investments that exchanged massive flows of the collected and/or accumulated surpluses into the Gulf, Chinese, and other foreign investors, whereas the poorest African most targeted recipients were the least benefitted. Despite the ambiguity and scarcity of accessible information on the Gulf/African businesses, we have heavily drawn available facts from United Nations and international sources, as well as critical views by Pan- African scholars, human rights’ activists, and political opponents. To ensure sustainable development free of exploitation and abuse of authority for the African peoples, foreign investors should avoid the past colonial and/or neocolonial ventures that dispossessed the land and manpower of the Continent, reinstated wealth-and-power thirst rulers in authoritative systems of rule, and impoverished indigenous farmers and the low-income workers and professionals with lasting poverty.